ANALISIS PENGARUH PAD, DAU, DAK, DAN BELANJA PEMBANGUNAN TERHADAP PERTUMBUHAN EKONOMI, KEMISKINAN, DAN PENGANGGURAN: PENDEKATAN ANALISIS JALUR - Setiyawati, Anis; Hamzah, Ardi (UI Scholars Hub, 2007)
The purpose o f this research is to examine directly the effect of region original revenue, general fund allocation, specific fund allocation, and capital expenditure on economic growth; to examine directly the effect of economic growth on poverty and unemployment; and to examine indirectly the effect of region original revenue, generalfund allocation, specific fund allocation, and capital expenditure on poverty and unemployment. The samples of study are region expense and revenue budget in 2001 - 2005 at 38 municipal The result of study with regression was indicated that region original revenue and generalfund allocation have directly significant effect at level 0,01 on the economic growth, economic growth have directly significant effect at level 0.01 on the poverty, and the unemployment, the region original revenue and general fund allocation have indirectly significant effect on the poverty and the unemployment.